Estimation of target hazard quotients and potential health risks for metals by consumption of shrimp (Litopenaeus vannamei) in Selangor, Malaysia - Shantakumari Rajan,; Nur Safiyyah Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The concentrations of the heavy metal in Pacific white shrimp (Litopenaeus vannamei) purchased from the local wet markets throughout the state of Selangor were investigated using flame atomic absorption spectrometry. The order of the heavy metal concentrations were Zn>Cu>Pb>Cd, whereby the metal concentrations in most samples exceeded the limits of the Malaysian Food Regulation, 1985 and the guidelines set by the Food and Agriculture Organisation (1983). A health risk analysis based on the mean target hazard quotient (THQ) yielded values <1 for all metals for average and maximal consumers. The total THQ (tTHQ) which measures the aggregated risk due to heavy metal uptake via the ingestion of L. vannamei was 0.124 and 0.372 for average and maximal consumers, respectively. This suggests that although the metal concentrations are exceeding the limit, there is no calculated significant risk from metal toxicity by the consumption of shrimp.